HPLC analysis of laxative rhein content in cassia fistula fruits of different provenances in Thailand - S. Chewchinda (2018)
The ripe fruit pulp of Cassia fistula Linn. (Fabaceace), which is locally called Khun or Ratchaphruek in Thailand, has long been used as a traditional laxative drug due to its anthraquinone glycosides constituent. Rhein is the major anthraquinone in the fruit pulp while minor constituents are aloin and sennosides. The aims of this study were to develop and validate a high performance liquid chromatographic method for quantitative determination of rhein content in the fruit pulp of C. fistula collected from different provinces in four main parts of Thailand. Chromatographic separation was performed on a BDS Hypersil C18 column (250×4.6 mm, i.d. 5 μm). The isocratic mobile phase was 0.5% aqueous acetic acid solution and methanol (40:60) with the flow rate of 1.0 mL min -1 . The UV detector monitored at 435 nm. This method was validated for linearity, precision, accuracy, limit of detection (LOD) and limit of quantitation (LOQ). The proposed HPLC method showed acceptable validation parameters. The correlation coefficient value was 0.999, confirming the linearity of the method. The R.S.D value was lower than 2% and the average recovery of rhein was 99.12±0.33% indicated the precision and accuracy of the method, respectively. Rhein content in the fruit pulp of C. fistula collected from 10 different provinces in Thailand was found in the range of 17-44 mg% w/w (average 37.6 mg% w/w). This validated HPLC method was sensitive, precise and accurate for quality assessment of raw materials of C. fistula fruit pulp and its products.